Prognóstico e desfecho clínico em pacientes com melanoma in situ e melanoma fino - Joao Renato Vianna Gontijo (2021)
Background: there is a lack of data regarding the possibility and rate of local recurrence (LR) and metastasis in patients with melanomas in situ (MIS) and thin melanomas (TM) (Breslow thickness ≤ 1.0 mm), as well as risk factors associated with these initial tumors. Objectives: to assess the prevalence and features of patients with MIS and TM who had LR, metastasis or death by melanoma. Methods: this is an observational, retrospective study with MIS and TM, diagnosed in a 23-years-period (1997 to 2020) at the Department of Dermatology from Oregon Health and Science University, United States of America; Dermatology Service of Hospital das Clínicas from Faculdade de Medicina da Universidade Federal de Minas Gerais, Brazil and a private office at Brazil. Features such as sex, age, familial history of melanoma, follow-up duration, tumor site (head and neck, anterior trunk, posterior trunk, upper extremities, lower extremities and acral), number of melanomas, death due to melanoma, occurrence of non melanocytic neoplasms (basal cell carcinoma and squamous cell carcinoma), Breslow thickness, and their relation with LR, metastasis or death, were analyzed. Fisher's Exact test was used to identify independent prognostic factors. Survival curves were calculated using the Kaplan-Meier estimator and compared with the log-rank test. Results: 1122 patients were analyzed, metastasis rate was 1.3% (n = 14), and the initial tumor was MIS in only two patients; the other 12 (85.7%) were TM. LR rate was 1.9% (n = 21), and in this group, 66.7% were MIS and 33.3% TM. Breslow thickness was associated with worse prognosis (p = 0.01) and overall survival rate was worse in patients with MIS located in the head and neck (p = 0.03). In TM, this relationship was worse in tumors located at the posterior trunk and head and neck (p = 0.008). Average follow-up time in the LR group was 121,7 months 121,7 months (60,3 ± 5,8 months 95% CI [5,8 - 246,1]) and 102,2 months (102,2 ± 77,7 months 95% CI [16,1 - 236,1]) in patients that had metastasis. During clinical follow-up, 31.9% of patients had at least one basal cell carcinoma and 22.9% of patients had at least one squamous cell carcinoma. Conclusion: the results demonstrate that despite the good prognosis in patients with TM and MIS, in some cases they can be aggressive and have the ability to metastasize. Findings of other neoplasms during follow-up combined with recurrence data suggest the need for long-term medical surveillance in patients with melanoma.